The Life Experiences of Non-Muslim Students at Muhammadiyah University: A Phenomenological Study on Inclusive Islamic Education - Yusuf, Muhammad; Pajarianto, Hadi; Halim, Ibrahim; Amriani; Zhang, Miao (Al-Hayat: Journal of Islamic Education, 2025)
This study aims to explore the experiences of non-Muslim students at Muhammadiyah University of Palopo within the context of inclusive Islamic education and to develop a relevant and contextual conceptual model. A qualitative approach with a hermeneutic phenomenological design was employed to investigate students' subjective experiences through in-depth interviews, participatory observation, and document analysis. The main findings include the adaptation process of non-Muslim students, which begins with a "culture shock" and transforms into acceptance and integration; Al-Islam and Kemuhammadiyahan courses serve as arenas for negotiating meaning and identity, with diverse perceptions; patterns of identity negotiation are categorized as assertive, adaptive, and compartmentalized identities; transformative experiences emerge in cognitive, affective, and behavioural dimensions; and institutional support varies among universities, with institutions in urban-pluralistic areas demonstrating more systematic inclusive policies. Based on these findings, an inclusive Islamic education model was developed that integrates Islamic values with principled inclusivity, encompassing structural, pedagogical, relational, and spiritual dimensions. This research makes an original contribution by expanding the concept of inclusivity in Islamic education and offering an operational framework for the transformation of moderate and inclusive Islamic education in Indonesia. The study's limitations regarding location and resource context form the basis for recommendations for further testing.